PEMBUATAN PRODUK HOME CARE DAN EDUKASI KEBERSIHAN LINGKUNGAN UNTUK MENINGKATKAN KEMANDIRIAN KESEHATAN DAN PEREKONOMIAN MASYARAKAT DI KELURAHAN SUBANGJAYA KECAMATAN CIKOLE KOTA SUKABUMI - Mulyani, Reni; Indah Anwar, Devi; Setiono, Setiono (Universitas Mataram, 2024)
Subangjaya Village, in Cikole District, Sukabumi City, faces significant air pollution issues that impact the cleanliness of clothing and the health of its residents. This pollution increases the risk of respiratory disorders, especially for those with pre-existing health conditions. To address this issue, this community service program aims to raise awareness about the importance of cleanliness and provide training on making household care products, such as liquid laundry soap and aloe vera-based shampoo. The program targets TP-PKK administrators through educational methods and training, which include distillation techniques, product labeling, and the production of soap and shampoo. The education focuses on the importance of maintaining environmental and clothing cleanliness to reduce the impact of air pollution. This training is expected to improve family skills and economic conditions, as the products created can be used independently or sold, reducing dependence on commercial products. Additionally, the program involves lecturers and students from the Muhammadiyah University of Sukabumi, fostering synergy between academics and the community. The expected outcomes include improved health, skills, and economic conditions for the community, as well as a reduction in the impact of air pollution. This program also supports the achievement of Key Performance Indicators (KPI) by enhancing environmental awareness and collective well-being. Overall, the program contributes to better health, cleanliness, and family economy, as well as an improved quality of life for the residents of Subangjaya.